Próba wyboru książek, pozostawiających ślad w naszym życiu. Analiza preferencji czytelniczych słuchaczy Nauczycielskiego Kolegium Języków Obcych we Wrocławiu - Romulska, Joanna (eBooki.com.pl, 2014)
The issue of choosing books which leave meaningful traces on our lives is a significant one. The contemporary publishing market is flooded with new releases and information about them. It is increasingly difficult to pick books which are worth reading. The aim of the study is to analyse reading preferences among students of the Teacher Training College (a post-secondary school) and attempt a selection of books which have in some way contributed to changes in the readers’ lives. The resultant list includes both books which have influenced the recipients in a positive way and publications which the students would not recommend due to a negative impact on their moods and emotions. The research was conducted by means of surveys, on a sample of 127 respondents. Their responses and opinions led to addressing the following questions: what is the position of reading among other ways of spending their free time, what is the general reading activity of the students, how many books a month they read, whether they read books in electronic form, whether they listen to audiobooks, what books and disciplines they are interested in, what motivates them to read, what sources of access to books they have, how they learn about books which are worth reading, what difficulties they face in accessing books, how they select books to read, what makes them choose a particular book, what are the names of their favourite authors, what are the titles of their favourite books, whether they have books to which they return (and if so, which ones), whether there are books which have left meaningful traces on their lives and what has changed after reading them, whether there are books they would not recommend and why, whether there are authors the respondents reject as a rule, and whether their parents used to read to them in childhood. The results of the study are worth considering, especially by those working with young people at the post-secondary level. The knowledge of book titles preferred by the students, as well as their favourite and rejected authors, may facilitate the work of a bibliotherapist.
Keywords: bibliotherapy; reader surveys; reading preferences; readership